Influence of the Economy on Political Decisions: The Case of Lula Da Silva’s Inaugural Speech in 2023 - Gonzalez, Rafael Barbera; Garcia, Cesar (Transformations In Business & Economics, 2025)
The main objective of this paper is to analyze how political discourse, with a strong economics and transformational approach, reaches different audiences. Specifically, we study Luiz Inácio Lula da Silva's speech at the National Congress on January 1, 2023, marking his inauguration as president of Brazil. The audiovisual content of the speech is used to investigate, through a codebook, the reality of the market environment in Brazil. The purpose is not only to analyze the competitiveness of political and economic discourse in an international context saturated with diverse messages but also to assess its contributions to the development of Brazilian society. The conclusions of this work confirm the research questions. On the one hand, Lula's discourse resonates more strongly with ideologically aligned audiences. On the other hand, he employs both verbal and nonverbal variables that help him reach the audience more efficiently.